Inflammation and Medicinal Plants-An Ethnomedicinal Approach - R. Ramasubramaniaraja, B. Parimala Devi, N. Tamilchelvan (Journal of Phytology, 2010)
There is an increasing demand for the medicinal plants in developing countries like India. Attention need to be given to assess the medicinal value of such plants to explore the potential drugs out of it. Inflammation is the condition associated with many of the disease states and this review elaborate the medicinal plants, their parts used in the effective management of Inflammation and its associated conditions. Ã‚Â